ANALISIS LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP KINERJA PERAWAT RSUD PETALA BUMI PEKANBARU - Muzammil, Aidil; Hendriani, Susi; Noviasari, Henni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to analyze the influence of environmental variables and workload on the performance of hospital nurses Petala Earth Pekanbaru. This study was conducted from December 2013 to January 2014.In this study consisted of three variables: the dependent variable and two independent variables. These variables are performance (Y), of environmental work (X1) and workload (X2). The study was conducted using a sample of 56 people. Research using census sampling technique by giving questionnaires to the respondents. In terms of data analysis, descriptive study using qualitative methods to explain the results of the study. Known to the state of Earth's Hospital Petala very necessary to have an increased viability of hospitals Petala Earth for environmental issues. More conducive and good, then the nurse will feel comfortable in the work. Further to the workload in hospitals Petala Earth itself for the nurses felt not too big, but it is necessary to continually evaluate in order to implement an appropriate system for the nurses in that workload is not too heavy and can make the job go well and maksimam especially in caring for the patient. For most affect the performance of the nurses were working environment compared to the workload of nurses hospital Pekanbaru Petala Earth, for the work environment is a major concern for improving the performance of the nurses..Keywords: Work Environment, Work Load, Performance